Polymorphism of Clinical Manifestations in Patients with “the Nutcracker Syndrome” - Nesterenko, Iryna Romanivna (Journal of Education, Health and Sport, 2021)
Introduction. “The nutcracker syndrome” occurs due to abnormal compression of the left renal vein (LRV) between the superior mesenteric artery and the aorta. Clinical manifestations range from hematuria, proteinuria, pain in the left lumbar region, left sided varicocele in men, and left sided pudendal varicosity in women to the development of severe anemia and renal failure in some cases due to progressive phlebohypertension. Materials and methods. The study included 210 patientswith suspected “nutcracker syndrome” . The age of the patients ranged from 12 to 52. All patients were interviewed for specific complaints. All referred patients underwent color Doppler ultrasound. The patients with confirmed left renal vein stenosis underwent CT angiography. Results of the research According to color Doppler ultrasound, different degree of aorta mesenteric clamp (AMC) was confirmed in 138 (65.7%) patients, critical LRV stenosis was observed in 35 of them. The predominant complaints of the patients with AMC included pain in the left half of the abdomen and left lumbar region, left sided varicocele and left sided pudendal varicosity, hematuria.. More than half of the patients with AMC complained of dysmenorrhea, and one in four patients with AMC complained of erectile dysfunction. Conclusions. There is no consensus on the diagnostic algorithm for this pathology detection. There is a lack of evidence base (multicenter clinical randomized trials) regarding the clinical selectivity of treatment approaches. The pathology is rarely diagnosed due to a number of objective and subjective reasons, nonspecific symptoms, and therefore it deserves special attention in the study of pathogenesis, diagnosis and choice of treatment approach.